การประเมินศักยภาพการคืนพลังงานไฟฟ้าสำหรับระบบขับเคลื่อนลิฟต์ - เกียรติสุขคณาธร, ไพบูลย์; คล้ายดี, กิตติพงศ์; วัจนเทพินทร์, นภัทร (RMUTSB ACADEMIC JOURNAL, 2016)
บทความนี้นำเสนอการประเมินศักยภาพการคืนพลังงานไฟฟ้าสำหรับระบบขับเคลื่อนลิฟท์ เพื่อใช้เป็นข้อมูลในการติดตั้งชุดคืนพลังงานไฟฟ้าสำหรับการอนุรักษ์พลังงาน ในบทความได้แสดงการวิเคราะห์การทำงานของมอเตอร์ ซึ่งสามารถแบ่งออกเป็น 2 โหมด คือ โหมดมอเตอริงและโหมดเจนเนอเรติง การประเมินศักยภาพการคืนพลังงานไฟฟ้าที่นำเสนอได้แสดงการตรวจวัดพลังงานไฟฟ้ าของลิฟต์จากการทำงานที่กำหนดโดยเงื่อนไขตามพิกัดโหลดและการเคลื่อนที่ขึ้นลง รวมทั้งการตรวจวัดพลังงานไฟฟ้าของลิฟต์จากการทำงานจริงตามปรกติด้วย ผลการวิจัยแสดงให้เห็นว่าระบบขับเคลื่อนลิฟต์สามารถคืนพลังงานไฟฟ้าได้ประมาณร้อยละ 6.42 ของการดึงพลังงานไฟฟ้า โดยการคืนพลังงานสูงสุดและการดึงพลังงานสูงสุดจะเกิดขึ้นในเงื่อนไขที่ลิฟต์เคลื่อนที่ขึ้น และลงตัวเปล่าตามลำดับ นอกจากนั้นผลการวิจัยยังแสดงให้เห็นว่าทุกๆ ครั้งที่ลิฟต์เบรกจะมีการคืนพลังงานไฟฟ้าอีกด้วย ลักษณะดังกล่าวหากติดตั้งชุดคืนพลังงานไฟฟ้ากับระบบลิฟต์เดิมเพื่อคืนพลังงานกลับไปยังระบบของการไฟฟ้าจะทำให้สามารถอนุรักษ์พลังงานซึ่ง จะเกิดความคุ้มค่าในระยะยาว Potential assessment of the energy regeneration for an elevator drive system This paper presents the potential assessment of the energy regeneration of an elevator drive system to set up the regenerative module for energy saving. In this paper, an analysis of the motor function was shown. It can be separated into 2 modes which consisted of the motoring mode and the regenerating mode. The proposed potential assessment of the energy regeneration, the measurements of energies from the conditional determination of the elevator function and normal elevator function were shown. The results revealed that the elevator drive system cold regenerate energies about 6.42% of the absorbed energies. The maximum energy regeneration and absorption would be coincided with 0% of the rated capacity for the movement of the elevator going up and down consequently. Moreover, the results also showed that the energy regeneration would be occurred every break. These findings represented that if the regenerative module was installed together with the conventional elevator system, it could save energies in long-term beneficially.